2015
DOI: 10.1159/000430388
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy Plays a Protective Role in Advanced Glycation End Product-Induced Apoptosis in Cardiomyocytes

Abstract: Background/Aims: To investigate the effect of advanced glycation endproduct-induced autophagy in rat cardiomyocytes and to identify the role of autophagy in advanced glycation end product-induced cell apoptosis. Methods: After cultured rat cardiomyocytes were treated with advanced glycation end products (AGEs), protein expression was detected by western blotting, autophagosomes were observed by electron microscopy, the cell apoptotic rate was determined by flow cytometry, and cell variability was quantified by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…There are many studies on AGEs and autophagy; RAGE enhances autophagy in pancreatic cancer, HUVECs, cardiomyocytes (Kang et al, 2011;Chen et al, 2015;Hu et al, 2015). However, there are also contradictory conclusions that AGE dose-dependently decreases mesangial cell and hFOB1.19 cell viability and induces apoptosis (Chang et al, 2013;Meng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There are many studies on AGEs and autophagy; RAGE enhances autophagy in pancreatic cancer, HUVECs, cardiomyocytes (Kang et al, 2011;Chen et al, 2015;Hu et al, 2015). However, there are also contradictory conclusions that AGE dose-dependently decreases mesangial cell and hFOB1.19 cell viability and induces apoptosis (Chang et al, 2013;Meng et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Protein extraction and western blotting were performed as previously described [30]. In brief, 3×10 5 cells were seeded in 6-cm dishes and exposed to RA (0-6 μM) at different times.…”
Section: Protein Extraction and Western Blot Analysismentioning
confidence: 99%
“…Well-established type 1 diabetic animal models, namely STZ-induced diabetic mice [9] and OVE26 mice [10], exhibit inhibited of cardiac autophagy along with cardiomyocyte apoptosis and cardiac dysfunction. The crosstalk between autophagy and apoptosis is complex, and Hu et al revealed that autophagy or autophagy-related proteins can lead to apoptosis or autophagic cell death under certain conditions [11]. …”
Section: Introductionmentioning
confidence: 99%